The Enforcement of Criminal Laws of Hate Speech in Social Media - Feri Vernando Situngkir; Siti Rodhiyah Dwi Istinah (Law Development Journal, 2021)
The objectives of this study are as follows: To determine the law enforcement of hate speech crimes in social media. To find out the factors that hinder criminal law enforcement of hate speech in social media. This is to determine the efforts to overcome the obstacles to the enforcement of the hate speech criminal law. This study uses an empirical juridical approach, with descriptive analytical research specifications. The results of this study are law enforcement against hate speech offenders on social media starting from the first stage, namely the police. hate speech perpetrators then the next step is to the prosecutor's office, and the last stage of the trial. Penalties in the form of imprisonment and fines for hate speech offenders are expected to provide a deterrent effect on hate speech criminals on social media. Inhibiting factors, namely, Public Awareness Factors, Security Factors, Law Enforcement Factors. Efforts to overcome obstacles, namely Act No. 11 of 2008 which was later revised to Act No. 19 of 2016, the formation of a special division by the police that specifically handles cyber crime cases, the holding of a cyberpatrol to monitor activities on social media, and the establishment of a cyber agency. national to minimize the spread of negative content on social media, as well as the existence of government services to make it easier for the public to report cyber crime cases.